A real options model for loan portfolios of actively traded Philippine universal banks - Jackson J. Tan; Fernando L. Trinidad (Journal of Global Entrepreneurship Research, 2018)
This study applies Real Options Theory to banking in the environment of actively traded Philippine Universal Banks. These banks exist in an environment of imperfect information with regard to lending, and a country where credit scarcity impedes the growth and performance of entrepreneurial activity. We investigate the option premiums of loan portfolios that depict managerial flexibility with investment strategy. A Real Options Model that considers both the strategies to lend and to idle shows that smaller lending institutions will value loans higher than their larger competitors. From the model, the need to maintain smaller variances in loan portfolio returns constrains manager flexibility. Option premiums in the Philippines exhibit sensitivity to information asymmetries. In these findings, this discussion forwards three propositions and their implications. Furthermore, this paper discusses the value of a hedging portfolio to counter risks from information asymmetry. Hence, this paper differs from many models in the existing literature that focus just on the value of the call option, the value of expansion or growth.
Keywords: 650; Real options theory; Banking; Loan portfolio; Valuation; Strategy; Lending